Regulatory reforms and productivity performance of the Malaysian mobile telecommunications industry - Mohamad, Noorihsan (2004)
This paper explores the productivity performance of the Malaysian mobile telecommunications industry in the pre and post-reform environment particularly with the passage of both Communications and Multimedia Act 1998 (CMA 1998) and the Malaysian Communications and Multimedia Act 1998 (CMCA 1998). Productivity has been measured by the Malmquist index, using a Data Envelopment Analysis (DEA) technique. The Malmquist productivity measures are decomposed into two components: technological change and technical efficiency change index. The findings suggest that Total Factor Productivity (TFP) has increased significantly for the whole industry, predominantly in the post-reform period through the establishment of Malaysian Communications and Multimedia Commission (MCMC). Despite the positive productivity development that has taken place, the paper however found that technical progress has been the most important source of productivity growth to Malaysian mobile telecommunications industry. Low technical efficiency in the industry indicates a great potential for the industry to further increase its productivity through higher utilization of technology as well as technological knowledge dispersion. Thus, existing regulatory framework need to be redesigned to complement the productive capacity of technology to further promotes the growth of the Malaysian mobile telecommunications industry.